Regulating the local availability of tobacco retailing in Madrid, Spain: a GIS study to evaluate compliance. Issue 3 (10th July 2018) - Valiente, Roberto; Sureda, Xisca; Bilal, Usama; Navas-Acien, Ana; Pearce, Jamie; Franco, Manuel; Escobar, Francisco
Abstract : Background: In Spain, tobacco sales are limited to tobacco-exclusive stores and associated vending machines. A minimum of 150 m between stores is required, unless they exceed a legal sales threshold. Minimum distances to schools are recommended but not defined. We evaluated compliance with these regulations in Madrid, Spain. Methods: Information about tobacco-exclusive stores and their sales volume was obtained in 2014. We used geographic information system to identify stores closer than 150 m between them and examine whether they exceeded the sales threshold. We estimated distances between stores and schools, considering different distance intervals (<150 m, 150–300 m and >300 m) and calculations (crow flies and street network). We assessed the association of area-level demographic and socioeconomic characteristics with the distribution of tobacco stores. Results: 5.3% (34/638) of tobacco stores were within 150 m of each other. Among those, 76% (26/34) did not meet the regulation sales threshold. These stores were in areas with lower proportion of young population (<15 years) and higher proportion of people with university-level education. 75% (476/638) of stores were situated closer than 300 m to schools. No differences were identified in sociodemographic and economic characteristics by the store distance to schools. Conclusion: Most tobacco stores are compliant with the regulations in Spain. However, these regulations are insufficient to reduce tobacco availability. More restrictive regulations are needed to limit the geographic distribution of tobacco retailers, and health criteria should also be considered in the current legislation. The evaluation of the Spanish regulatory model may provide useful insights for other jurisdictions looking to decrease the tobacco retail availability.